An Update Review of Biosimilars of Adalimumab in Psoriasis – Bioequivalence and Interchangeability - Zhou X; Chen Z; Bi X (Dove Medical Press, 2021)
Xin Zhou,1 Zhuo Chen,2 Xinling Bi1 1Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of China; 2Department of Dermatology, Shanghai Children's Medical Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 200127, People's Republic of ChinaCorrespondence: Xinling BiDepartment of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of ChinaTel +86 13386278946Email bixinling@163.comAbstract: Biologic drugs have revolutionized the treatment of psoriasis and other rheumatological diseases. In recent years, many biosimilar agents that are highly similar in structure and function to their originator products have been developed, including the tumor necrosis factor-alpha antagonist adalimumab. The considerably lower cost of these products has greatly cut the economic burden of the patients and increased the accessibility of biologic therapies worldwide. The US Food and Drug Administration and/or the European Medicines Agency have approved eight biosimilars of adalimumab (ABP 501/BI 695501/SB5/GP2017/FKB327/MSB11022/PF-06410293/CT-P17) for the treatment of psoriasis, and others are under review. Given that these agents showed pharmacokinetic, efficacy, safety, and immunogenicity profiles comparable to those of the originator, adalimumab biosimilars were licensed for all indications approved for reference adalimumab based on extrapolation; however, some of the equivalence studies were only conducted in one or two disease populations. This review discusses the bioequivalence of adalimumab biosimilars as demonstrated by various clinical trials, the extrapolation of indications, guidance and policies of the EU and US on interchangeability (nonmedical switching/automatic substitution) between biosimilars and originators, and the real-life practices of switching from reference adalimumab to the respective biosimilars. Further data from real-world studies and post-marketing analyses are needed better to address the efficacy and safety of the transition strategy.Keywords: biosimilar, adalimumab, psoriasis, guidance of interchangeability, extrapolation of indications